Effects of crowd size on referee decisions: Analysis of the FA Cup - Downward, P.; Jones, M. (Journal of Sports Sciences, 2007)
Data were collected on the number of first yellow cards awarded during 857 games, over six seasons (1996 - 2002), played in the Football Association (FA) Cup. Overall, a significantly higher number of yellow cards were awarded against the away team, while a non-linear relationship between crowd size and yellow cards was observed. In general, the probability of a yellow card being awarded against the home team decreased as crowd size increased, but was attenuated for the largest crowd sizes. Crowd size may be related to the probability of the home team receiving a yellow card in two potential ways. Crowd noise may be a decision-making heuristic whereby the likelihood that an incident is a foul is increased when accompanied by crowd noise. Alternatively, referees may seek to appease the crowd and are more likely to do so as crowd size increases. The present findings have implications for the training of match officials and for coaches and players as they prepare to play away from home.ub